30 YEARS OF THE MINERALOCORTICOID RECEPTOR: Mineralocorticoid receptor antagonists: 60 years of research and development. Issue 1 (July 2017) - Kolkhof, Peter; Bärfacker, Lars
Abstract : The cDNA of the mineralocorticoid receptor (MR) was cloned 30 years ago, in 1987. At that time, spirolactone, the first generation of synthetic steroid-based MR antagonists (MRAs), which was identified in preclinical in vivo models, had already been in clinical use for 30 years. Subsequent decades of research and development by Searle & Co., Ciba-Geigy, Roussel Uclaf and Schering AG toward identifying a second generation of much more specific steroidal MRAs were all based on the initial 17-spirolactone construct. The salient example is eplerenone, first described in 1987, coincidentally with the cloning of MR cDNA. Its launch on the market in 2003 paralleled intensive drug discovery programs for a new generation of non-steroidal MRAs. Now, 30 years after the cDNA cloning of MR and 60 years of clinical use of steroidal MRAs, novel non-steroidal MRAs such as apararenone, esaxerenone and finerenone are in late-stage clinical trials in patients with heart failure, chronic kidney disease (CKD), hypertension and liver disease. Finerenone has already been studied in over 2000 patients with heart failure plus chronic kidney disease and/or diabetes, and in patients with diabetic kidney disease, in five phase II clinical trials. Here, we reflect on the history of the various generations of MRAs and review characteristics of the most important steroidal and non-steroidal MRAs.